Organic carbon and nitrogen stocks along a thermokarst lake sequence in Arctic Alaska - Fuchs, Matthias (Dr.); Lenz, Josefine; Jock, Suzanne; Nitze, Ingmar; Jones, Benjamin M.; Strauss, Jens; Günther, Frank (Dr.); Grosse, Guido (Prof. Dr.) (Journal of Geophysical Research: Biogeosciences, 2019)
Thermokarst lake landscapes are permafrost regions, which are prone to rapid (on seasonal to decadal time scales) changes, affecting carbon and nitrogen cycles. However, there is a high degree of uncertainty related to the balance between carbon and nitrogen cycling and storage. We collected 12 permafrost soil cores from six drained thermokarst lake basins (DTLBs) along a chronosequence north of Teshekpuk Lake in northern Alaska and analyzed them for carbon and nitrogen contents. For comparison, we included three lacustrine cores from an adjacent thermokarst lake and one soil core from a non thermokarst affected remnant upland. This allowed to calculate the carbon and nitrogen stocks of the three primary landscape units (DTLB, lake, and upland), to reconstruct the landscape history, and to analyze the effect of thermokarst lake formation and drainage on carbon and nitrogen stocks. We show that carbon and nitrogen contents and the carbon-nitrogen ratio are considerably lower in sediments of extant lakes than in the DTLB or upland cores indicating degradation of carbon during thermokarst lake formation. However, we found similar amounts of total carbon and nitrogen stocks due to the higher density of lacustrine sediments caused by the lack of ground ice compared to DTLB sediments. In addition, the radiocarbon-based landscape chronology for the past 7,000years reveals five successive lake stages of partially, spatially overlapping DTLBs in the study region, reflecting the dynamic nature of ice-rich permafrost deposits. With this study, we highlight the importance to include these dynamic landscapes in future permafrost carbon feedback models. Plain Language Summary When permanently frozen soils (permafrost) contain ice-rich sediments, the thawing of this permafrost causes the surface to sink, which may result in lake formation. This process, the thaw of ice-rich permafrost and melting of ground ice leads to characteristic landforms-known as thermokarst. Once such a thaw process is initiated in ice-rich sediments, a ...